METHODOLOGY OF ORGANIZING EDUCATIONAL WORK BASED ON INTERACTIVE METHODS. (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article discusses the methodology for organizing educational work based on interactive methods. The essence of interactive methods, their use in educational processes, their effectiveness and significance in modern education are analyzed. The article broadly covers the ways of implementing interactive methods in practice, their role in developing the moral, spiritual and social qualities of students and young people, and their role in organizing effective educational work.